2019
DOI: 10.1039/c9cp04147h
|View full text |Cite
|
Sign up to set email alerts
|

Periodically-arrayed ferroelectric nanostructures induced by dislocation structures in strontium titanate

Abstract: A new engineering method of ferroelectric nanostructures: ferroelectric nanostructures induced and controlled by dislocation arrangements in SrTiO3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Recent piezo-force-microscopy and nonlinear optical investigations indeed show that individual dislocation structures have local polarization 8,24 , while the polar displacements are not significantly affected by electron doping 25 . Furthermore, modeling suggests that local electric polarization is enhanced in extended dislocation structures 9 .…”
Section: Structure Of Plastically Deformed Stomentioning
confidence: 99%
See 1 more Smart Citation
“…Recent piezo-force-microscopy and nonlinear optical investigations indeed show that individual dislocation structures have local polarization 8,24 , while the polar displacements are not significantly affected by electron doping 25 . Furthermore, modeling suggests that local electric polarization is enhanced in extended dislocation structures 9 .…”
Section: Structure Of Plastically Deformed Stomentioning
confidence: 99%
“…Since the local atomic arrangement is very different in dislocation cores than in the bulk, the electronic properties around individual dislocations have been found to be significantly modified in a diverse set of quantum materials [6][7][8] . Such effects are expected to be strongly amplified when dislocations assemble into larger structures 9 , yet this is experimentally virtually unexplored.…”
mentioning
confidence: 99%
“…As one direction of the developments, the application of phase-field simulation has gradually expanded to a smaller scale. For example, phase-field simulation of dislocation dynamics, coupling between ferroelectricity and dislocations, and thermal activated skyrmion motions has been conducted [4][5][6] . Such developments of phase-field simulations have undoubtedly clarified many material properties at the nanoscale but diffusive time scale where molecular dynamics (MD) and quantum mechanical simulations can not access.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we propose defect engineering to achieve atomic-scale polar topological order, including skyrmion and merons, even below the critical size. Defect engineering provides various features in materials; furthermore, recent theoretical and experimental studies reported that manipulating oxygen vacancies in perovskite materials induces multiferroicity. Notably, ferroelectricity was observed in paraelectric ceramics SrTiO 3 . , The emergence of multiferroicity around atomic vacancies originates from significant local lattice distortions, which introduce local symmetry breaking in their vicinity. Thus, the observation of local ferroelectricity in SrTiO 3 induced by atomic vacancies holds potential for realizing polar topological order below the critical size.…”
mentioning
confidence: 99%